Termination of Employment: A Comprehensive Analysis of Legal Implications, Modalities, and Requirements - Laines Alvarez, Yolanda Maria; González Parra, Amelia Stefania; Gaona Angamarca, Emily Karolina (Revista Universidad de Guayaquil, 2026)
The study aims to analyze the main modalities for the termination of the employment relationship in Ecuador and their legal effects, with the purpose of identifying regulatory gaps and proposing adjustments that strengthen the protection of workers. The research was developed under a qualitative approach and a socio-legal design, using documentary, regulatory, jurisprudential, and comparative analysis. For this, legal provisions, ministerial agreements, administrative resolutions, labor sentences, and specialized national and international doctrine were reviewed. The findings showed that, although Ecuadorian legislation recognizes different forms of termination of the employment contract, including mutual agreement, visto bueno (approval/authorization), and the grounds attributable to the worker provided for in Article 172 of the Labor Code, relevant violations of due process persist. The strategic use of legal figures was observed to conceal dismissals without legitimate cause, especially to the detriment of vulnerable groups such as pregnant women and people with disabilities. Likewise, institutional limitations were identified in the supervision and control of labor termination procedures, which affects the real effectiveness of the guarantees provided in the current regulations. The study concludes that the Ecuadorian legal system requires reforms that not only update its content but also ensure the correct execution of norms and administrative procedures in labor matters. It is essential to promote a legal culture that recognizes work as a fundamental right and not merely as a contractual link susceptible to unilateral decisions.